Hydrogen sulfide generation and signalling in the heart and coronary artery of the pig - Al-Taie, Yasir Yaseen Taha (2021)
Cardiovascular diseases (CVD), such as hypertension, angina, myocardial infarction, arrhythmia, heart failure, and stroke, are some of the most common causes of death around the world. Hydrogen sulfide (H2S) is considered as a bio-modulator gasotransmitter molecule. In recent years, evidence that H2S may have an influential role in several important biological processes, especially in the cardiovascular system (CVS) has increased. Many studies have reported the production of H2S within the body. H2S appears to play a role in the regulation of vascular tone. Therefore, there is accumulated evidence regarding the role of H2S in the vasculature, while there is little information about the role of H2S in the heart. Many cardiovascular pathologies have been associated with low H2S production, such as hypertension, ischaemic heart diseases (IHD), and atherosclerosis.